White light phosphorescence from ZnO nanoparticles for white LED applications. (1st September 2022) - Das, Sagnik; Ghorai, Uttam K.; Dey, Rajib; Ghosh, Chandan K.; Pal, Mrinal
Abstract : Point defect-mediated, reproducible, stable, and intense white phosphorescence from a single-phase solid has been reported for the first time. Abstract : White light emission from a pristine, solid material is currently the biggest challenge in the lighting industry. In this paper we report for the first time highly reproducible, stable, and intense white phosphorescence (∼4–32 μs) from phase-pure zinc oxide (ZnO) nanopowder synthesized by a simple, low temperature process. The structure and morphology were studied by XRD, FESEM, and TEM. The white light consisted of narrow blue (centered at ∼425 nm) and broad yellow-orange (centered at ∼625 nm) photoluminescence and the best result was observed at (0.36, 0.33) in the CIE plot. The presence of zinc interstitial (Zni ) and oxygen interstitial (Oi ) defects responsible for such white phosphorescence was confirmed by EDX, XPS, and Raman studies. The visibly bright white emission has appreciable quantum yield (∼12–14%) and cool/near cool correlated color temperature, rendering it suitable for W-LED applications. Further, a defect chemistry-based thermodynamic interpretation was invoked to adequately explain the white emission.